Pengaruh Jenis Scrap Besi Sebagai Bahan Utama Pengecoran Logam Terhadap Komposisi Dan Kekerasan Besi Cor - Doni Saputra, Agus Riyana; Pratama, Dimas Fandi; Rachman, Firman Fauzi (Unit Penelitian, dan Pengabdian Masyarakat (UPPM) Politeknik ATI Makassar, 2025)
Scrap metal waste is a type of metal waste that comes from production processes, construction, or items that are no longer used. Although this waste is often considered a useless material, it has great potential to be recycled and reused in the foundry industry, especially in the manufacture of cast iron and other iron products. The scrap metal recycling process has significant economic benefits, such as reducing the need for primary raw materials and saving energy. In scrap metal, the element content varies depending on the type of scrap metal used, the source of the waste, and previous processes that may have changed the chemical composition of the material. For example, scrap metal that comes from metal products with low carbon content, such as low carbon steel, will produce recycled products with low hardness and low bending ability. On the other hand, scrap metal from cast iron or high carbon steel produces products with better hardness properties but lower strength. Cast iron is a type of metal that is widely used in the manufacturing industry for maintenance and production processes. Therefore, in this research, an analysis of the hardness test of cast iron material made from scrap iron will be carried out using the Rockwell Method.